Implementasi Amanat Agung dalam Penginjilan dan Pemuridan terhadap Pertumbuhan Gereja Berdasarkan Matius 28:18-20 - Sinaga, Janes; Sinambela, Juita Lusiana; Sagala, Rudolf Weindra; Nainggolan, Bartholomeus Diaz (Tumou Tou, 2023)
The purpose of this study is that everyone is involved in implementing the Great Commission of Jesus Christ so that church growth occurs. The harvest is a lot but the workers are few, this is the Word of our Lord Jesus Christ. To produce a harvest of souls that are won for Christ, the Great Commission in Matthew 28:18-20 must be carried out namely “Go” (Preach) and Make disciples (Discipleship). Evangelism is the first step as a disciple. And being a disciple is an activity that aims to motivate and train spiritually mature believers to devote themselves wholeheartedly to God in order to become disciples. Evangelism and discipleship are one and cannot be separated. Evangelism is the first step as a disciple. If every church and its members carry out this great commission well, it will bring many people to come to Christ and this has an impact on the growth of the church. The book of Matthew was originally addressed to early Christians but God's Word is still relevant in every age, because the essence of the Word always directs everyone to believe Jesus is the savior of mankind. This study uses a qualitative method, by collecting data and information from various library sources such as the Bible, spiritual books and journals which are concluded and used in this research so as to lead everyone to carry out the Great Commission so that the church can grow well.